Analisis Kandungan Logam Timah (Sn), Timbal (Pb) dan Kromium (Cr) Dalam Buah Kemasan Kaleng Secara Spektrofotometri Serapan Atom - Subardi Bali; Denia Pratiwi; Aisyah Fadhiah Zaroh (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Processed fruits that are packaged in cans which aims to extend the durability of the fruit. Usually, heavy metals are used as the constituent materials of the cans, namely tin as the body of the can, lead to connect the lid and body of the can and chromium to coat the tin. So it is necessary to pay attention to safety and its effect on canned fruit packaging. This study was conducted to determine the feasibility of canned packaged fruit for consumption and compare the results with the provisions of the Food and Drug Administration regulation number 9 of 2022. The samples used were canned peach, canned longan and canned lychee. The samples were taken randomly in Pekanbaru with different expiry dates. Samples were analyzed by atomic absorption spectrophotometry. Tin metal concentrations in PKK 1, PKK 2, KKK 1, KKK 2, LKK 1 and LKK 2 were 209.90 mg/kg, 190.13 mg/kg, 151.75 mg/kg, 86.75 mg/kg, 250.57 mg/kg and 116.19 mg/kg respectively. lead metal concentrations were only found in KKK 1, KKK 2 and PKK 2 at 0.042 mg/kg, 0.0083 mg/kg and 0.11 mg/kg respectively. The chromium metal content in the samples in order are 0.36 mg/kg, 0.42 mg/kg, 0.80 mg/kg, 0.21 mg/kg, 0.22 mg/kg and 0.52 mg/kg of canned packaged fruit that has metal levels exceeding the threshold of tin metal in sample LKK 1, lead metal in sample PKK 2, and KKK 2 and chromium with samples PKK 1, KKK 1 and LKK 2. It is concluded that canned packaged fruit is not suitable for consumption. Because it exceeds the limit of the provisions of the Food and Drug Administration regulation number 9 of 2022